Graphene-based active metasurface with more than 330° phase tunability operating at mid-infrared spectrum. (March 2021) - Sun, Zhanshan; Huang, Fumin; Fu, Yunqi
Abstract: Metasurfaces composed of subwavelength optical antennas offer fruitful functionalities to manipulate the amplitude, phase and polarization of light. Sufficient phase tunability of metasurfaces has significant potential for dynamic beam steering, hologram and flat optics exhibiting tunable focusing. Here, we demonstrate a graphene based metasurface that gives rise to more than 330° smooth and continuous phase modulation at mid-infrared spectrum. The phase modulator model introduces multiple resonances including Split-Ring-resonator (SRR) resonance and inductance-capacitance (LC) resonance, leading to the outstanding sensitivity of the metasurface to tiny change of surrounding electromagnetic environment. Through adjusting the Fermi level of the monolayer graphene beneath the resonators, both scattered amplitude and phase can be efficiently modulated, so that the electrically programmable metasurface enables nearly arbitrary manipulation of scattered wavefront. Electro-optically tunable focusing and beam steering are numerally realized by constructing one dimensional discrete array element. The phased array design achieves an average efficiency up to 22% within 60° steering range. The reflective focusing lens with focal lengths of 10 μm, 15 μm and 20 μm are successfully demonstrated, respectively. The proposed metasurface has promising potential in optoelectronic applications such as imaging, sensing and focusing. Graphical abstract: Image 1